Reinterpretation of variant of unknown significance in the clinical setting of inherited cardiac conditions. (3rd October 2022) - Novelli, V; Manzoni, M; Sommariva, E; Colombo, G; Biondi, M L; Mushtaq, S; Farina, S; Roberto, M; Pizzamiglio, F; Casella, M; Pompilio, G
Abstract: Introduction: In the last years, genetic testing for inherited cardiac conditions (ICCs) is expanded and evolved at an incredible rate. This tool may inform treatment options and lifestyle choices to avoid arrhythmia triggers. Furthermore, identifying the genetic underpinning of the disorder improves risk assessment for asymptomatic or pre-symptomatic family members. However, despite the large numbers of disease-causative genes identified in the last years, only 60% of the patients with a clinical diagnosis of ICCs carry a pathogenic or likely pathogenic variant. The remaining 40% of the cases have an inconclusive or ambiguous test caused by negative results or mainly by the identification of one or more variants of unknown significance (VUS). In this case, the test results are uninformative and clinically irrelevant, increasing uncertainty about medical management. Purpose: We investigated whether a periodic re-evaluation of the detected VUS, using the American College of Medical Genetics and Genomics (ACMG) criteria, may impact the clinical setting of patients with suspected ICC and their family members. Methods: We reevaluated 306 consecutive probands with suspected ICC undergoing genetic testing by next-generation sequencing using the Illumina TruSight Cardio Sequencing panel, from 2017 to 2021. Results: Thirty-five percent of patients carried at least one variant in a gene associated with the phenotype. Of these, 94 had been previously classified as VUS and were not considered clinically actionable. After an average time of 36 months, they were reevaluated and 26.6% of the VUS were reclassified. In particular, 1 was downgraded to Benign and 24 were upgraded to Likely Pathogenic (16) or Pathogenic (8). According to the different phenotypes, the reclassification rate was 45.8% in Hypertrophic cardiomyopathy, 33.3% in Dilated cardiomyopathy, 27.3% in Arrhythmogenic cardiomyopathy, 12.5% in Brugada syndrome, and 50% in Long QT syndrome patients. This reclassification process allowed to recategorize 24 probands as clinically and molecularly diagnosed and to extend the genetic screening to their at-risk family members. Conclusions: Given the extent of the clinical impact that genetic testing can have, these findings suggest that a periodic reevaluation of genetic test results, particularly VUS, should be a mandatory step in the ICC diagnostic workflow. Funding Acknowledgement: Type of funding sources: None.